Breast cancer patterns by age groups in Brazil: insights from population-based registries data - Jessé Lopes da Silva; Luiz Claudio Santos Thuler; Andréia Cristina de Melo (BMC Cancer)
Abstract Background Breast cancer (BC) has exhibited varied epidemiological trends based on distinct age categories. This research aimed to explore the incidence and mortality rates of BC within pre-defined age groups in the Brazilian population. Methods BC incidence trends were assessed from 2010 to 2015 using Brazilian Population-Based Cancer Registries, employing age-standardized ratios and annual average percentage change (AAPC). Hospital-Based Cancer Registries provided clinical and sociodemographic data from 2000 to 2019. Mortality data were obtained from the National Mortality Information System from 2000 to 2020. Three groups were compared: < 40, 40–69, and ≥ 70 years. Results From 2010 to 2015, 205,966 new BC cases were recorded, with incidence rates of 7.1/100,000 for < 40, 156.5/100,000 for 40–69, and 247.5/100,000 for ≥ 70 years. The < 40 years group exhibited a significant increase in incidence rate (AAPC + 1.6; 95% CI: 1.0 to 2.2; p < 0.001). This age group also showed a higher proportion of black patients (53%, p < 0.001), alcohol consumption (20.5%, p < 0.001), proportion of patients treated at stages ≥ IIB (64.0%, p < 0.001), and a higher likelihood of receiving multiple treatment modalities (60.7%, p < 0.001). The ≥ 70 years group experienced a longer delay exceeding 60 days from diagnosis to treatment onset (54%, p < 0.001), while exhibiting a higher proportion of endocrine therapy utilization (45.3%, p < 0.01). Mortality rates increased across all subgroups, with the < 40 years group showing the most pronounced increase (AAPC + 1.8%; 95% CI: 1.6 to 2.1; p < 0.001). Conclusion These results highlight marked disparities in BC incidence, mortality rates, clinicopathological and sociodemographic characteristics between women under 40, and those in the 40–69 and ≥ 70 age groups in Brazil.